Relationships between Foreign Subsidiaries Competition and Cooperation in Multinational Plant Engineering Companies - Maurer, Julia (Gabler, 2011)
International business scholars have conducted a considerable amount of research on both headquarters-subsidiary relationships and subsidiary roles. The horizontal relationships between foreign subsidiaries, however, have not gained much attention, although these linkages are important to the Multinational Corporation (MNC). Business practice shows that subsidiaries can cooperate and/or compete with one another, and that their relationships differ even across companies operating in the same industry. Julia Maurer offers the first comprehensive conceptual and empirical approach to the topic. She develops a novel framework for the analysis of intersubsidiary relationships and applies it to the large-scale plant engineering industry. The empirical study confirms that an MNC`s strategic orientation has a considerable impact on its intersubsidiary relationships.